THE EFFECT OF APPLYING LEARNING MODEL ON NATURAL SCIENCE COMPETENCE: LITERATURE STUDY ABOUT SNOWBALL THROWING - Ayu Wulandari; Heffi Alberida; Ardi Ardi; Rahmadhani Fitri (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This research is motivated by the low activity and learning outcomes of students in learning. Learning is still teacher centered. Student do activities outside of learning. We need a model to motivate student in learning. The model can be used is Snowball Throwing.The purpose of writing this article is to  look at the correlation of the application of the Snowball Throwing model to student outcomes. This research methode by reviewing journal uses 5 journal with ISSN. Dewi's research (2015) states that the Snowball Throwing model assisted by interactive multimedia has an effect on student learning outcomes. Handayani's research (2017) states that the Snowball Throwing model has an influence on student learning outcomes. Fitri's research (2017) states that the Snowball Throwing model with word square media has a positive influence on the activities and learning outcomes of students. Najla (2017) and Purba (2020) state that there are differences in learning outcomes between classes that use Snowball Throwing and those that don't. Thus it shows the Snowball Throwing model has a correlation with the learning outcomes of students.